Value of contrast-enhanced ultrasound assisted core needle biopsy in the diagnosis of cervical lymph node tuberculosis - Li, Jun; Li, Dan; Zhang, Wenzhi (Frontiers in Oncology, 2025)
AimTo investigate the value of contrast-enhanced ultrasound (CEUS) assisted core needle biopsy (CNB) in the diagnosis of cervical lymph node tuberculosis (LN TB) and improve the positive rate of cervical LN TB.MethodsWe retrospectively analyzed 730 samples obtained from July 2010 to January 2025 from patients treated with effective antituberculosis therapy and with microbiologically confirmed and surgical pathologically proven cervical lymph node enlargement who had undergone CEUS- CNB at our hospital. All patients were divided into two groups according to the historical control method. The CEUS group (2017–2025) underwent CEUS- CNB (485 cases), whereas the US group (2010–2018) underwent US-guided CNB (245 cases). The positive rates of pathological diagnosis and Xpert Mycobacterium tuberculosis complex (MTBC) and resistance to rifampin (RIF) (MTB/RIF) assay diagnoses were compared between the groups.ResultsThe specimens’ integrity was significantly higher after CNB in the CEUS group than in the US group (CEUS group: 72.30%; US group: 45.49%), and visual satisfaction of sampling in the CEUS group was higher (χ2: 47.651, P < 0.001). Histopathological examination sensitivity, specificity, positive predictive value, and negative predictive value were higher in the CEUS group than in the US group. The sensitivity of the Xpert MTB/RIF assay was significantly higher in the CEUS group than in the US group.ConclusionThe study results support the clinical use of CEUS for improving the diagnostic performance and positive rate for cervical LN TB.